Adaptation to Climate Change in Europe and Central Asia Agriculture - Sutton, William R.; Block, Rachel I.; Srivastava, Jitendra (World Bank, Washington, DC, 2017)
To ensure the viability and competitiveness of agriculture and forestry and sustain rural livelihoods, it is critical to take stock of the impacts of climate change on rural sectors in Europe and Central Asia (ECA) countries and implement appropriate adaptive measures. The interactions between the weather-sensitive agriculture and forestry sectors, climate change, and the natural resource base are highly complex and deserve special attention. Globally, the increased frequency of heat stress, droughts and flooding events caused by climate change threaten to reduce crop yields and livestock productivity in many areas, while increased risks of fires and pest outbreaks will have negative consequences for forests. In this paper, the authors examine the exposure, sensitivity, and adaptive capacity of ECA agriculture to climate change, and provide recommendations for addressing the challenges of climate through adaptation. We have made use of the best available climate change projections to categorize countries in the region by likely agricultural sector impacts. We have also attempted to synthesize information from the literature on climate change adaptation in agriculture in order to identify the most relevant points for ECA countries, including options for technical, institutional and policy measures. Based on this initial assessment, there are plans to support World Bank clients in carrying out assessments and developing strategies at the country level in the near future.